BIM–LCCA Integration for Road Pavement Maintenance. Issue 6 (June 2022) - Oreto, Cristina; Biancardo, Salvatore Antonio; Veropalumbo, Rosa; Viscione, Nunzio; Russo, Francesca; Dell'Acqua, Gianluca
The use of building information modeling (BIM) for infrastructures is on the rise but the use of the life cycle cost analysis (LCCA) integrated within the BIM environment itself to analyze multiple design alternatives and set up a proper maintenance plan has not yet been developed. It is possible to integrate evaluation of maintenance and waste recovery strategies, minimizing costs and the use of raw materials. A visual programming tool was exploited to set up an application that applies the LCCA methodology to a road pavement project in the early design phase, returning the total maintenance cost updated to the year of construction, the number of maintenance interventions, and the residual value of accumulated fatigue damage. The execution of the LCCA tool dynamically updates the properties of the BIM model with the resulting pavement management plan and returns multiple outputs, giving to the user the possibility of making further assessments and store the data as needed. The developed application shows that BIM is a promising tool to implement more complex and useful analyses that can reduce the maintenance planning time and allow the designer to choose between multiple alternative solutions already in the early design phase, bringing consistent cost savings through the possibility of finding the minimum cost solution based on the specific project needs in compliance with the quality and safety criteria to be guaranteed for the road category.